The biocompatibility and antifungal effect of Rosmarinus officinalis against Candida albicans in Galleria mellonella model - Meccatti, Vanessa Marques [UNESP]; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Pereira, Thaís Cristine [UNESP]; de Lima, Patrícia Michelle Nagai [UNESP]; Abu Hasna, Amjad [UNESP]; Senna, Lavinia Barbosa [UNESP]; Marcucci, Maria Cristina [UNESP]; Junqueira, Juliana Campos [UNESP]; de Oliveira, Luciane Dias [UNESP] (Springer Nature, 2022)
This study was performed to evaluate the biocompatibility and antifungal effect of Rosmarinus officinalis against Candida albicans in Galleria mellonella model. Five different concentrations of R. officinalis glycolic extract (50; 25; 12.5 e 6.25 mg/mL) were used to evaluate its biocompatibility in G. mellonella model, in which the nystatin suspension (100; 50; 25; 12.5 e 6.25%) was used as a control group. The antifungal action of R. officinalis glycolic extract was evaluated on C. albicans for 72, 48 and 12 h at two different phases: (1) using the extract as therapeutic agent; and (2) using the extract as prophylactic agent. PBS was used as a negative control group. G. mellonella survival curves were plotted using the Kaplan–Meier method and statistical analysis was performed using the log-rank test (Mantel–Cox) and the significance level was set at (α ≤ 0.05). There was no significant difference among the groups in which all were biocompatible except of a significant death rate of 26.6% with nystatin 100%. In phase 1, it was found that after 7 days, there was no statistically significant difference among the prophylactic treatment groups. In phase 2, the groups of R. officinalis 6.25 mg/mL for 72 h and R. officinalis of 12.5 mg/mL for 24 h promoted the survival rate of the larvae in comparison with the control group with a significant difference (p = 0.017) and (p = 0.032) respectively. Therefore, R. officinalis extract is biocompatible in different concentrations and can be used as a prophylactic agent against fungal infection.